Influence Of Modern Wounding Techniques; Honey in Healing Chronic Wounds - Lazdia, Wenny; Mohd Said, Faridah; Nambiar, Nisha; Hasnita, Evi; Rinawati Kasrin, Rinawatix; Dewi, Ratna (Journal of Neonatal Surgery, 2025)
Introduction: Wounds are damage to or disorders of the skin. Honey can be used to treat wounds, increasing the activity of the immune system, encouraging debridement, and stimulating wound regeneration. Aim: The purpose of this study was to find out whether modern wound dressing techniques and honey affected the process of healing chronic wounds in the work area of the Bukittinggi City Health Center. Method: This research is quantitative with a Quasi-Experimental design and Group Pretest – Posttest Design approach. This study's population included all patients who were indicated to have chronic wounds in the working area of the Bukittinggi City health center. It was conducted in March 2023. The sample size was 10 people. Sampling was done using purposive sampling, and the data was analyzed using univariate and bivariate analysis. Findings: The results of the univariate analysis showed that the average chronic wound before being given the honey intervention was 37 and the average chronic wound healing after being given the honey intervention was 24.3. The results of the Bivariate analysis showed that there was an effect of modern wound dressing techniques; honey in the process of healing chronic wounds (Pvalue = 0.000). Conclusion and recommendation: So, there is an influence of modern wound dressing techniques; honey in the process of healing chronic wounds in the working area of the Bukittinggi City health center. It is expected that respondents will apply modern wound dressing techniques; honey to heal chronic wounds and pay attention to personal hygiene in patients.